Antihypertensive activities of standardised Moringa oleifera Lam. (Merunggai) extracts in spontaneously hypertensive rats - Endang Kumolosasi,; Cheng, Chen Wei; Anis Zafiqa Abdullah,; Nur Syahirah Abd Manap,; Woon, Lee Lee; Mohd Hanif Yusuf,; Lo, Shin Ying; Fhataheya Buang,; Mazlina Mohd Said,; Hazni Falina Mohamad,; Malina Jasamai, (Penerbit Universiti Kebangsaan Malaysia, 2021)
In recent years, Moringa oleifera has received commercial interest for its blood pressure (BP)-lowering effect. The objectives of this study were to investigate the hypotensive, diuretic, and angiotensin converting enzyme (ACE)-inhibitory activities of M. oleifera ethanolic and aqueous extracts. Spontaneously hypertensive (SH) and normotensive (NT) rats were fed the ethanolic and aqueous extracts at a dose of 1000 mg/kg each for 14 days. The rats were allocated to 12 groups of five rats each. Systolic and diastolic BP were measured, and urine was collected. All extracts, except the aqueous stem extract, significantly reduced systolic and diastolic BP in SH rats, but none of the extracts showed significant hypotensive effects on NT rats. The ethanolic leaf extract (ELE) caused significant diuresis. Moreover, most of the extracts inhibited ACE activity significantly at 40 and 80 µg/mL. ELE, aqueous leaf extract (ALE), and ethanolic pod extract (EPE) showed the highest levels of inhibition (>50%), and their IC50 values; ELE (58.65±1.55), ALE (71.35±1.00) and EPE (54.04±1.00) were determined. The hypotensive effect observed was achieved either by diuretic or ACE-inhibitory activity. The active extracts are worthy of further investigation, as they have the potential to be developed as dietary supplements for pre-hypertensive individuals.